AN EFFECTIVE WAY TO ASSESS STUDENT KNOWLEDGE IN THEORETICAL MECHANICS - Mahmudov Zokirjon Sotivoldievich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
It is important to use modern methods in the assessment of theoretical mechanics in higher educational institutions. The proposed method for fair determination of students' knowledge level and increasing their activity in classes using the method of interactive confused logical chain. By using the method for one subject, section and whole part of the science of theoretical mechanics, the possibilities of fair, transparent and quick assessment of students' knowledge level are shown.